PKM Pemanfaatan Facebook Canvas Sebagai Tools Pemasaran Produk Pada Cynara's Corner - Nasrulloh Isnain; Reza Avrizal; Heru Sulistiono (LPPM Universitas 17 Agustus 1945 Semarang, 2022)
Today there are various kinds of social media for business. Some examples social media for business including Facebook, Youtube, Blogs, Instagram, Twitter, Snapchat. From a variety of social media that are often used by business actors is facebook. Facebook users in Indonesia reach 129.9 million in early 2022. This figure is derived from advertising reach sources Facebook to Indonesian users. Thus, the percentage of users Facebook in Indonesia is equivalent to 46.8 percent of the total population in early 2022. In the world of marketing, social media plays an important role is very important in building a strong customer base for a brand. One of the biggest in Indonesia, of course, is Facebook. In to increase marketing channels, there are recommendations for tools and software Free Facebook marketing at its best. We don't need to spend money to subscribe or buy existing Facebook marketing tools is wrong one is Facebook Canvas.